Chest computed tomography findings for a cohort of children with pulmonary Langerhans cell histiocytosis. Issue 10 (25th July 2020) - Della Valle, Valeria; Donadieu, Jean; Sileo, Chiara; Barkaoui, Mohamed Aziz; Héritier, Sébastien; Brisse, Hervé; Boutry, Nathalie; Tréguier, Catherine; Chateil, Jean‐François; Petit, Philippe; Pracros, Jean‐Pierre; Chastagner, Pascal; et al.
ABSTRACT: Objective: This study was undertaken to describe the spectrum of lung computed‐tomography (CT) findings in children with pulmonary Langerhans cell histiocytosis (PLCH) and to evaluate for this population the CT‐scan nodule and cyst scores proposed by adult pulmonologists at diagnosis and during follow‐up. Methods: Among 175 children with PLCH identified in the French national population‐based Langerhans cell histiocytosis cohort, 60 were retrospectively selected by the availability of CT for a central review by three pediatric radiologists. These 60 patients are representative of childhood PLCH for almost all clinical aspects, except a lower percentage of risk organ involvement (38% vs 54%; P = 0.05). Results: The 60 children's chest CT scans ( n = 218) were reviewed. At diagnosis, 63% of them had nodules, 53% had cysts, and 29% had both. The percentages of patients with nodules or cysts increased from diagnosis to peak disease activity, respectively, from 63% to 73% and from 53% to 66%. The costophrenic angle was involved in 71%. Patients with pneumothorax (25%) had a higher median cyst score. Alveolar consolidation was observed in 34%. Patients with low CT‐scan nodule and cyst scores had no long‐term pulmonary sequelae. Conclusions: Well‐known characteristics of adult PLCH (nodules and cysts) were observed in children. The chest CT scores proposed by adult pulmonologists could easily be applied to childhood PLCH. Lesions in children, unlike those in adults, are frequently located near the costophrenic angles. Alveolar consolidation might be considered an atypical feature of childhood PLCH.